(untitled) (Research, Society and Development, 2020)
This article notes the precariousness of research on the history of state professional education, with regard to the collection and critic of sources, taking as an example the Escola Profissional Masculina da Capital (São Paulo). Founded in 1911 to qualify and nationalize the workforce, and directed for 23 years by the educator Aprigio Gonzaga, its contribution remains associated with backward and empirical procedures. The creation of the Superintendence of Professional Education in 1934 is considered the ground zero of this teaching, for reformulating it according to guidelines of the Rational Labor Organization. São Paulo Public Education Survey, carried out by Fernando de Azevedo, in 1926, was one of the strategies responsible for the consensus; therefore, it will be analyzed in this article.